Digital transformation of the agrifood system: Quantifying the conditioning factors to inform policy planning in the olive sector. (September 2021) - Parra-López, Carlos; Reina-Usuga, Liliana; Carmona-Torres, Carmen; Sayadi, Samir; Klerkx, Laurens
Abstract: Despite the growing importance of the digital transformation (DT) of the agrifood sector on the political agenda, traditional policies are not enough to provide proactive responses to rapid technological changes and new approaches for policy planning are necessary especially at regional level. This manuscript proposes and illustrates the implementation of a new methodological framework for DT policy planning in the case of Andalusia, the olive world leader region, but applicable to other regions and sectors, with two objectives: 1) to quantitatively determine the importance of the conditioning factors of DT in the olive sector in the short/medium term, by developing an AHP/SWOT/PESTLE model, and 2) to design public policies to strengthen the DT, taking advantage of the potentialities and alleviating the deficiencies, by carrying out a quantitative TOWS analysis. The knowledge of diverse groups of experts, i.e. stakeholders in the sector, has been used in all analyses due to the lack of reliable data and the complex nature of the issues analysed. The results show that the opportunities and strengths are more prominent than weaknesses and threats for DT. Environmental issues stand out as an opportunity to boost DT. There is also a growing interest in developing an interoperability strategy which is an opportunity to overcome the low technological integration of the value chain. DT can also enable a more transparent value chain and improved traceability. Some negative factors are the lack of evidence on the economic viability of investment in digital technologies, shortage of labour and young farmers, and potential unintended and unanticipated effects of DT. Important policies strategies to foster DT are: improving environmental efficiency though DT; promoting youth employment in the sector; enhancing coordination among innovation actors; developing a common interoperability strategy; and fostering technological integration in the sector. Highlights: An AHP/SWOT/PESTLE model is developed to analyse the conditioning factors of DT. DT of the Andalusian olive sector in Andalusia has an optimistic outlook. Opportunities and strengths outweighing weaknesses and threats. Policy strategies for DT should focus on environmental efficiency and youth employment. Greater coordination and technological integration of actors are also needed.